2003
DOI: 10.1038/nm834
|View full text |Cite
|
Sign up to set email alerts
|

Benfotiamine blocks three major pathways of hyperglycemic damage and prevents experimental diabetic retinopathy

Abstract: Three of the major biochemical pathways implicated in the pathogenesis of hyperglycemia induced vascular damage (the hexosamine pathway, the advanced glycation end product (AGE) formation pathway and the diacylglycerol (DAG)-protein kinase C (PKC) pathway) are activated by increased availability of the glycolytic metabolites glyceraldehyde-3-phosphate and fructose-6-phosphate. We have discovered that the lipid-soluble thiamine derivative benfotiamine can inhibit these three pathways, as well as hyperglycemia-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
610
3
35

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 729 publications
(673 citation statements)
references
References 28 publications
25
610
3
35
Order By: Relevance
“…Here, we present the results of a clinical case study showing the potential of benfotiamine as a disease-modifying drug for AD. As a derivative of thiamine with better bioavailability, benfotiamine has been demonstrated to exert beneficial effects against abnormal glucose metabolism and its consequences via multiple mechanisms, including the elimination of oxidative stress [16,17] and the inhibition of glycogen synthase kinase-3 [18], which are both considered to be major pathogenic factors that cause neurodegeneration in AD. The better bioavailability and the pharmacological effects via multiple mechanisms against abnormal glucose metabolism and its consequences may explain why benfotiamine administration but not thiamine supplementation [24] had a long-term beneficial effect on cognitive ability in AD patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we present the results of a clinical case study showing the potential of benfotiamine as a disease-modifying drug for AD. As a derivative of thiamine with better bioavailability, benfotiamine has been demonstrated to exert beneficial effects against abnormal glucose metabolism and its consequences via multiple mechanisms, including the elimination of oxidative stress [16,17] and the inhibition of glycogen synthase kinase-3 [18], which are both considered to be major pathogenic factors that cause neurodegeneration in AD. The better bioavailability and the pharmacological effects via multiple mechanisms against abnormal glucose metabolism and its consequences may explain why benfotiamine administration but not thiamine supplementation [24] had a long-term beneficial effect on cognitive ability in AD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Benfotiamine is a synthetic thiamine derivative with better bioavailability than thiamine and has been shown to prevent abnormal glucose metabolism via multiple pathways [16,17]. Our previous study demonstrated that benfotiamine improves cognitive impairment in a mouse model of AD (amyloid precursor protein/presenilin-1 (APP/PS1) transgenic mice) [18].…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…Cusick et al (28) has clearly shown that Vitamin E in dietary formulation (in dose of 500 IU daily) could reduce age related eye disease (ARED). Benfotiamine has been shown to block three major pathways of hypoglycemic damage and prevent diabetic retinopathy in experimental animals (29). Beside hypoglycemic control familial and genetic factors have been stressed to take part in the pathogenesis of complications like nephropathy and retinopathy (30).…”
Section: Discussionmentioning
confidence: 99%
“…In the diabetic retina, RAGE is predominantly upregulated in glia cells [101]. While the understanding of RAGE and its role in retinal dysfunction in diabetes and/or activation of pro-inflammatory pathways is less complete than in other organ systems, increasing evidence indicates that RAGE contributes to cellular perturbations in the retina [102][103][104]. Remarkably, in each of these models, protection from development of the pathological features was more profound in wild-type mice treated with sRAGE than in Rage −/− mice.…”
Section: Rage In Late Diabetic Complicationsmentioning
confidence: 99%